The Psychological Bridge to Exhaustion: Nomophobia Mediates the Link Between FoMO and Digital Fatigue in Digital Natives - Syukriati; Mardianto, Mardianto (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: The "always-on" culture of digital natives has accelerated the rise of digital fatigue, yet the underlying mechanisms transforming social anxiety into physical and mental exhaustion remain under-explored. This study investigates the mediating role of nomophobia—the fear of being without a mobile phone—in the relationship between Fear of Missing Out (FoMO) and digital fatigue. Utilizing a large-scale survey (N = 1,324) of Indonesian digital natives, mediation analysis reveals that nomophobia serves as a critical psychological bridge, accounting for a significant indirect effect in the FoMO-fatigue pipeline. By synthesizing Social Cognitive Theory and Cognitive Load Theory, our findings demonstrate that the compulsive drive for social connectedness systematically depletes cognitive and emotional resources. These results suggest that digital wellbeing interventions must move beyond simple "screen time" limits to address the underlying nomophobic anxiety that fuels exhaustion. This study provides a theoretical framework for developing targeted mindfulness-based interventions to mitigate the psychological toll of hyper-connectivity Keywords: Fear of Missing Out (FoMO), digital fatigue, digital native, nomophobia